Pengaruh Circuit Games Terhadap Peningkatan Kerjasama Tim pada Atlet Karate Majenang - Rachmawan, Rizki Aditya; Rezha, Mohamad; Kurniawan, Asep Ridwan; Kardani, Gani (Universitas Galuh, 2023)
The research to be carried out has a goal by the formulation of the problem set, namely